Cartographies on COVID-19 and functional divisions of the territory: an analysis on the evolution of the pandemic based on Basic Health Areas (BHA) in Castile and Leon (Spain) - Gonzalo Andrés López; Daniel Herrero Luque; Marta Martínez Arnaiz (Boletín de la Asociación de Geógrafos Españoles, 2021)
In the face of the confusion and uncertainty that COVID-19 has caused over the last year, Geography has proven to be a useful aid in the interpretation of the spatial dynamics that explain the transmission of the virus. Applied cartography and GIS analysis of epidemiological data have been consolidated as essential tools for interpreting the health crisis. This paper explores the usefulness of maps for the study of the evolution of the pandemic in Castile and Leon, one of the Spanish regions with the highest levels of infection and mortality. Based on the statistical variables of sick and dead people at the scale of the Basic Health Area (BHA), a first analytical approach is carried out by means of a sequence of dynamic maps during the first wave. Afterwards, a systematic study is carried out using thematic mapping for the period of the three waves, a period between March 2020 and March 2021. The analysis unravels the differential impact of the disease between rural and urban areas and reveals the problems of the mismatch between the functional divisions of the territory (BHA, as units of health analysis) and the scale of administrative management (municipalities, as the effective scale of action).